2019
DOI: 10.1039/c9cc03943k
|View full text |Cite
|
Sign up to set email alerts
|

An integrated Re(i) photocatalyst/sensitizer that activates the formation of formic acid from reduction of CO2

Abstract: cis-[Re(bpy)2(CO)2]+OTf− is a new integrated photosensitizer/catalyst for the selective visible light promoted photocatalytic reduction of CO2 to yield formic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…To achieve a high activity in photocatalytic CO 2 conversion, it is essential to develop satisfactory photosensitizers that have large absorption cross sections in the visible region and are capable of promoting efficient multiple electron transfer processes. Recent studies on precious metal-based PS (such as Ru, Ir, and Re) have shown good activity for CO 2 reduction [12][13][14][15][16][17][18][19][20][21][22][23][24][25] . However, molecular chromophores comprising earth-abundant elements usually give relatively low turnover numbers (TONs), which is a significant limitation in developing inexpensive AP systems [26][27][28][29] .…”
mentioning
confidence: 99%
“…To achieve a high activity in photocatalytic CO 2 conversion, it is essential to develop satisfactory photosensitizers that have large absorption cross sections in the visible region and are capable of promoting efficient multiple electron transfer processes. Recent studies on precious metal-based PS (such as Ru, Ir, and Re) have shown good activity for CO 2 reduction [12][13][14][15][16][17][18][19][20][21][22][23][24][25] . However, molecular chromophores comprising earth-abundant elements usually give relatively low turnover numbers (TONs), which is a significant limitation in developing inexpensive AP systems [26][27][28][29] .…”
mentioning
confidence: 99%
“…Several examples of single-active-site photocatalysts that function as both the photosensitizer and catalyst for CO 2 reduction based on Re, Os, Ir, Ru, and other metals have been reported. The development of self-photosensitized metal complexes is advantageous in terms of lowering the activation energy of the catalytic reaction and controlling its selectivity; thus, extensive efforts have been devoted to designing new molecular photocatalysts by changing the metal center and/or ligands.…”
mentioning
confidence: 99%
“…As expected, the reactivity of the photocatalytic system increased (TON FA of 2750), where at the same time the selectivity slightly dropped (88%). 71 In conclusion, switching from Earth abundant metal catalysts to Ir-and Re-based photocatalysts ensured higher TONs (TON FA > 2000). Compared to the Rh-based catalysts, the activity was lower, but the selectivity increased to almost 90%.…”
Section: Manganese Complexesmentioning
confidence: 83%